The comparison of two different strategies of intravitreal conbercept for polypoidal choroidal vasculopathy in Chinese patients results from a 48‐week randomized phase 4 study: STAR study. Issue 3 (18th October 2022) - Li, Xiaoxin; Qu, Jinfeng; Su, Guanfang; Yu, Suqin; Zhang, Yongjin; Sadda, Srini Vas; ,
Abstract: Purpose: To compare a treat‐and‐extend (TAE) strategy with a fixed dosing regimen of intravitreal conbercept (IVC) for the management of treatment‐naïve polypoidal choroidal vasculopathy (PCV) patients. Methods: 249 patients with treatment‐naïve PCV were randomized 1:1 to fixed dosing regimen with injections every 12 weeks (3 + Q12W) group or treat‐and‐extend regimen(3 + TAE) group. Patients received 3 monthly intravitreal injections of 0.5 mg conbercept as loading dose in both groups. The 3 + Q12W patients were monitored monthly and received mandated injections every 12 weeks; the 3 + TAE patients were monitored and treated monthly until the resolution of exudative disease activity; the interval between visits was then individualized according to study protocol. Visual and anatomical outcomes were compared between the two groups. Results: At 48 weeks, there was no significant difference between the 3 + Q12W group and 3 + TAE group in mean BCVA improvement ( p  = 0.421), mean changes in central retinal thickness (CRT) ( p  = 0.818), maximum retinal thickness (MRT) ( p  = 0.448), pigment epithelial detachment (PED) height ( p  = 0.221), PED volume ( p  = 0.076), branching vascular network (BVN) area ( p  = 0.615), polypoidal lesion number ( p  = 0.701), polypoidal lesion area ( p  = 0.424), rates of patients who avoided vision loss of ≥15 ETDRS letters ( p  = 0.397) or complete polypoidal lesion regression rate (43.8% vs. 41.8%, p  = 0.814). The 3 + Q12W group had more decreased retinal haemorrhage area ( p  = 0.014) and fewer mean numbers of injections comparing with 3 + TAE group (6.6 vs. 9.4, p  < 0.001). Mean maximum extension interval between injections after loading injections was 9.6 ± 2.0 weeks for 3 + TAE group, with 27.8% of patients achieving an extension interval of 12 weeks and 61.1% patients 8 weeks or more. Conclusions: Both 3 + Q12W and 3 + TAE regimens of IVC could result in improvement in visual and anatomical outcomes in PCV patients.